Problem Based Learning Assisted by Sangkar Bumi Props to Improve IPAS Learning Activity and Outcomes for Grade V Elementary School Students - Yusak Suryawan; Sudarmiani Sudarmiani; Yudi Hartono (CV. Edujavare Publishing, 2026)
Education is a cornerstone in shaping the future of the younger generation and a conscious effort to optimally develop individual potential. This study aimed to improve fifth-grade students’ learning outcomes in Science and Social Studies (IPAS) on Indonesia’s geographical location through the implementation of the Problem Based Learning (PBL) model assisted by Sangkar Bumi teaching aids. This Classroom Action Research (CAR) employed the Kemmis and McTaggart spiral model, consisting of planning, acting, observing, and reflecting. The participants were 32 fifth-grade students at SDN Pare 3, Kediri Regency. Data were collected through observation sheets, learning outcome documentation, and multiple-choice tests, then analyzed using descriptive qualitative and quantitative methods. The findings revealed that the PBL model assisted by Sangkar Bumi teaching aids effectively improved both the learning process and student achievement. The average learning outcome score increased from 60.31 in the pre-cycle (15.63% mastery) to 72.97 in Cycle I (50.00% mastery), and further to 83.84 in Cycle II with 100% classical mastery. Student learning activity also improved from 62.28% (Fair) in Cycle I to 87.61% (Very Good) in Cycle II, while teacher implementation increased from 71.43% to 92.86%. These results indicate that the PBL model supported by Sangkar Bumi teaching aids effectively enhances students’ engagement and learning outcomes in geographical location topics.